Participatory and community archives: the case of the Archivio Sonoro di Comunità in San Cesario (LE, Italy) - Olimpia Di Domenico; Irene Panarese (piano b, 2025)
Beginning with a natural renewal of archival practice, the late XXth century saw the emergence of a series of “new” archives that inevitably challenged the traditional discipline. One kind of archive, in particular, seems to have gone to meet the general need, which has affected contemporary art and society, to encourage the active participation of citizens, or rather the community, in the creation, transmission and preservation of their memory. Archives of this kind, called participatory archives, present innovative characteristics, such as the heterogeneity of the materials, very often on digital format, the absence of the archival bond and of the archivist’s figure, but what allows their birth is a precise voluntary act from the community of reference, now in the front row in the attempt to leave a trace of its own past. This paper therefore aims to describe participatory and community archives, starting with the definition of the role and meanings of community and memory, and then proposing a case of a participatory archive in Italy, the Archivio Sonoro di Comunità in San Cesario (LE).